Implementasi Sistem Mutu ISO-9000 Terhadap Kinerja Puskesmas di Kota Palu - Syamsuddin, Syamsuddin (Media Eksakta, 2009)
The goal, hence method of data collecting used is census method, type of research deskriptif-verifikatif, method of research of explanatory survey, technique used is cross sectional, and also object in this research is performance of puskesmas TQM in Palu City. Result of first hypothesis examination (product aspect) indicating that system of quality of ISO-9000 from product aspect by parsial have an effect on positive to performance of puskesmas TQM in Palu City that is equal to 0.215 or 21.5 gratuity; with the detail is level of direct influence that is 27.0 gratuity, and also the level of indirect influence which is passing aspect of action and aspect of management role that is (- 5.6) gratuity. Result of first hypothesis examination (action aspect) indicating that system of quality of ISO-9000 from execution aspect by parsial have an effect on the negative to performance of puskesmas TQM in Palu City that is equal to (-0.121) or (-12.1) gratuity; with the detail is level of direct influence that is 6.3 gratuity, and also the level of indirect influence which is passing aspect of product and aspect of management role that is (-0.184) gratuity. Result of first hypothesis examination (aspect of management role) indicating that system of quality of ISO-9000 from aspect of management role by parsial have an effect on positive to performance of puskesmas TQM in Palu City that is equal to 0.443 or 44.3 gratuity; with the detail is level of direct influence that is 56.3 gratuity, and also indirect influence which is passing aspect of product and action aspect that is (-12.0) gratuity. Â Result of second hypothesis examination indicate that the system of quality of ISO-9000 (product aspect, action aspect, aspect of management role) by simultan have an effect on to performance of puskesmas TQM in Palu City that is equal to 53 gratuity, and also 47 gratuity determined by external variable is which not studied.